Promoting Sustainability and Social Responsibility Through HRM in Neonatal Surgical Care - Sangeetha, K.; Vembar, Vanathi (Journal of Neonatal Surgery, 2025)
The role of Human Resource Management (HRM) in promoting sustainability and social responsibility has become increasingly significant in the healthcare sector, especially within neonatal surgical care where ethical, environmental, and patient-centered practices are paramount. This paper explores the strategic integration of HRM practices in advancing sustainability and fostering a socially responsible culture in neonatal surgical settings. By examining how core HR functions—such as recruitment, training, performance management, and employee engagement—can be tailored to support sustainability and Corporate Social Responsibility (CSR) objectives in neonatal care, this study emphasizes HRM's vital role in enhancing patient outcomes, workforce well-being, and community trust. Through a review of literature and healthcare-specific case studies, the research identifies effective HRM strategies that promote green practices, ethical leadership development, and social outreach within neonatal surgical units. The study also addresses the unique challenges and ethical considerations of implementing sustainable HRM in the high-stakes, resource-intensive environment of neonatal surgery. Findings suggest that healthcare organizations that proactively align HRM with CSR and sustainability not only contribute to societal and environmental well-being but also benefit from improved employee morale, enhanced organizational reputation, and strengthened patient trust. This paper provides practical insights for HR professionals and healthcare leaders seeking to build socially responsible, sustainable, and patient-focused neonatal surgical care teams..